Recommendations on the practice of calibration, dosimetry, and quality assurance for gamma stereotactic radiosurgery: Report of AAPM Task Group 178 - Petti, Paula L.; Rivard, Mark J.; Alvarez, Paola E.; Bednarz, Greg; Daniel Bourland, J.; DeWerd, Larry A.; Drzymala, Robert E.; Johansson, Jonas; Kunugi, Keith; Ma, Lijun; Meltsner, Sheridan G.; Neyman, Gennady; et al. (Medical physics (Lancaster), 2021)
The American Association of Physicists in Medicine (AAPM) formed Task Group 178 (TG‐178) to perform the following tasks: review in‐phantom and in‐air calibration protocols for gamma stereotactic radiosurgery (GSR), suggest a dose rate calibration protocol that can be successfully utilized with all gamma stereotactic radiosurgery (GSR) devices, and update quality assurance (QA) protocols in TG‐42 (AAPM Report 54, 1995) for static GSR devices. The TG‐178 report recommends a GSR dose rate calibration formalism and provides tabulated data to implement it for ionization chambers commonly used in GSR dosimetry. The report also describes routine mechanical, dosimetric, and safety checks for GSR devices, and provides treatment process quality assurance recommendations. Sample worksheets, checklists, and practical suggestions regarding some QA procedures are given in appendices. The overall goal of the report is to make recommendations that help standardize GSR physics practices and promote the safe implementation of GSR technologies.